PEMANFAATAN TIKTOK DALAM STRATEGI PEMASARAN: STUDI KASUS NAUGHTY INDONESIA DAN PELATIHAN TIM PEMASARAN DIGITAL - Antonius Felix; Devi Yurisca; Agung Stefanus Kembau; Julius Sutrisno; Fandevi Maitri (LPPM Universitas Bina Bangsa, 2024)
The use of social media, especially TikTok, has become an effective strategy for Naughty Indonesia in expanding its marketing reach and building close relationships with consumers. Through a proactive and creative approach, Naughty Indonesia has succeeded in building a strong brand image and increasing brand awareness among consumers. The training held for Naughty Indonesia's digital marketing team in the use of TikTok Ads also provided a deep understanding of the platform's potential as an effective marketing tool. The evaluation results showed a positive response from participants, with the majority giving a positive assessment of the quality and benefits of the activity. However, there are suggestions and inputs for further improvement and development, such as improved experiential practices and material development. In conclusion, this dedication succeeded in providing new insights for Naughty Indonesia in utilizing TikTok as an effective marketing strategy in the digital era. This not only provides benefits for the company, but also for the development of digital marketing team competencies in facing challenges and opportunities in the ever-evolving business world